2020
DOI: 10.3390/app10175895
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Modeling of COVID-19 in Saudi Arabia: Spread Projection, Awareness, and Impact of Treatment

Abstract: The first case of COVID-19 originated in Wuhan, China, after which it spread across more than 200 countries. By 21 July 2020, the rapid global spread of this disease had led to more than 15 million cases of infection, with a mortality rate of more than 4.0% of the total number of confirmed cases. This study aimed to predict the prevalence of COVID-19 and to investigate the effect of awareness and the impact of treatment in Saudi Arabia. In this paper, COVID-19 data were sourced from the Saudi Ministry of Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 37 publications
0
27
1
1
Order By: Relevance
“…Despite the success of network-based models, several published studies on COVID-19 modeling, including those supporting policy decision making, have focused on compartmental models [2][3][4][5][6][7][8][9][10][20][21][22][23]43]. Manzo [16] urged researchers to direct their efforts toward network-based SIR models and to start discussing a large-scale collection of empirical network data to foster such models.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the success of network-based models, several published studies on COVID-19 modeling, including those supporting policy decision making, have focused on compartmental models [2][3][4][5][6][7][8][9][10][20][21][22][23]43]. Manzo [16] urged researchers to direct their efforts toward network-based SIR models and to start discussing a large-scale collection of empirical network data to foster such models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several existing contributions modeled the COVID-19 outbreak in Saudi Arabia using different models [20][21][22][23]. For instance, Alboaneen et al [20] predicted that Saudi Arabia would have a maximum total cases of 79,000 using logistic growth and SIR models.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the infected cases (Figure 2A) and removed cases (Figure 2B) show a reasonable quality of fit. Since the optimization task led to local optima, we were guided by the results reported in [22,30,31] in selecting initial conditions and bounds on the fitted model parameters. The optimum values of model parameters are shown in Table 2.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…The challenge for data collection and fitting becomes more severe when the proposed model is highly structured. The balance between model structure and quality of fit was made clear in a number of studies concerning Saudi Arabia, where simple SIR models were shown to provide better fits to COVID-19 data than more complex network-based models [22,23].…”
Section: Introductionmentioning
confidence: 99%